Borders and the City: Intra-Urban Boundaries in Guangzhou (China) - Breitung, Werner (Quaestiones Geographicae, 2011)
Borders are fundamental structuring elements of space. This paper uses concepts derived from the study of political boundaries to make sense of urban structures and developments. It does this in the case of Guangzhou, a mega-city in Southern China, but the suggestion is that this approach is significant beyond the Chinese case. The author introduces five different ways to see borders (political, physical, socio-spatial, psychological and functional), and holds that border analysis should combine those five aspects. In the case of Guangzhou, spatially differentiated urban governance is seen as creating strong physical, social and other boundaries. This finding is illustrated by various pieces of evidence from the author's fieldwork, including survey data and qualitative interviews.